Safety of medication use in primary care. (22nd June 2014) - Olaniyan, Janice O; Ghaleb, Maisoon; Dhillon, Soraya; Robinson, Paul
Abstract: Background: Medication errors are one of the leading causes of harmin health care. Review and analysis of errors have often emphasized their preventable nature and potential for reoccurrence. Of the few error studies conducted in primary care to date, most have focused on evaluating individual parts of the medicines management system. Studying individual parts of the system does not provide a complete perspective and may further weaken the evidence and undermine interventions. Aim and Objectives: The aim of this review is to estimate the scale of medication errors as a problem across the medicines management system in primary care. Objectives were: To review studies addressing the rates of medication errors, and To identify studies on interventions to prevent medication errors in primary care. Methods: A systematic search of the literature was performed in PubMed (MEDLINE), International Pharmaceutical Abstracts (IPA), Embase, PsycINFO, PASCAL, Science Direct, Scopus, Web of Knowledge, and CINAHL PLUS from 1999 to November, 2012. Bibliographies of relevant publications were searched for additional studies. Key findings: Thirty-three studies estimating the incidence of medication errors and thirty-six studies evaluating the impact of error-prevention interventions in primary care were reviewed. This review demonstrated that medication errors are common, with error rates between <1% and >90%, depending on the part of the system studied, and the definitions and methods used. The prescribing stage is the most susceptible, and that the elderly (over 65 years), and children (under 18 years) are more likely to experience significant errors. Individual interventions demonstrated marginal improvements in medication safety when implemented on their own. Conclusion: Targeting the more susceptible population groups and the most dangerous aspects of the system may be a more effective approach to error management and prevention. Co-implementation of existing interventions at points within the system may offer time- and cost-effective options to improving medication safety in primary care.